2008
DOI: 10.1016/j.coph.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Congenital muscle disorders with cores: the ryanodine receptor calcium channel paradigm

Abstract: SummaryDysregulation of calcium signals due to defects of the skeletal muscle sarcoplasmic reticulum calcium release channel (ryanodine receptor; RyR1) is causative of several congenital muscle disorders including malignant hyperthermia (MH; MIM #145600), Central Core Disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
146
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 62 publications
2
146
0
Order By: Relevance
“…A single dominant missense mutation, Y128C, in the GlyR ␣1 subunit LBD, resulted in tonic channel opening in the absence of agonist. Spontaneous channel activity has been recognized as a pathogenic mechanism in other episodic disorders including congenital muscle disease, cardiac arrhythmias, and hypokalemic periodic paralysis (Paavola et al, 2007;Sokolov et al, 2007;Treves et al, 2008). Previous GlyR ␣1 site-directed mutagenesis studies have also identified three residues causing spontaneously opening: D97R and F99A in the LBD and A288W in M3 (Mihic et al, 1997;Beckstead et al, 2002;Miller et al, 2008).…”
mentioning
confidence: 99%
“…A single dominant missense mutation, Y128C, in the GlyR ␣1 subunit LBD, resulted in tonic channel opening in the absence of agonist. Spontaneous channel activity has been recognized as a pathogenic mechanism in other episodic disorders including congenital muscle disease, cardiac arrhythmias, and hypokalemic periodic paralysis (Paavola et al, 2007;Sokolov et al, 2007;Treves et al, 2008). Previous GlyR ␣1 site-directed mutagenesis studies have also identified three residues causing spontaneously opening: D97R and F99A in the LBD and A288W in M3 (Mihic et al, 1997;Beckstead et al, 2002;Miller et al, 2008).…”
mentioning
confidence: 99%
“…The first 4000 amino acids make up the large cytoplasmic domain that contains binding sites for various modulators, while the last 1000 amino acids constitute the carboxy terminal pore-forming domain [21,22]. Dominant and recessive mutations in RYR1, the gene encoding the RyR1, are associated with a range of early-onset neuromuscular disorders including the core myopathies central core disease (CCD) and multi-minicore disease (MmD), congenital fiber type disproportion, (CFTD) centronuclear myopathy (CNM), exertional rhabdomyolysis/myalgia as well as the pharmacogenetic disorder malignant hyperthermia (MH) [23][24][25][26].…”
Section: Excitation-contraction Couplingmentioning
confidence: 99%
“…Since this initial discovery in the early 90s, more than 200 mutations have been identified in patients with a variety of inherited myopathies including MHS, exertional rhabdomyolysis/myalgia and a range of congenital myopathies including CCD, as well as subgroups of MmD, CNM and CFTD [23][24][25][26]. Because of the sheer size of the RYR1 gene which spans 106 exons and >15 kb DNA, initial mutation searches were confined to hotspot domains originally implicated in autosomal dominant MHS and CCD.…”
Section: Disorders Associated With Ryr1 Mutationsmentioning
confidence: 99%
See 2 more Smart Citations